Missed Opportunities in the Prevention of First Esophageal Variceal Bleeding: A Real-World Clinical Audit of Undiagnosed and Under-Treated Patients - Yusuf Bünyamin Ketenci; Hakan Demiröz; Mehmet Akca; İbrahim Gören; Ufuk Avcıoğlu; Ahmet Bektaş (Journal of Clinical Medicine, 2026)
Background/Objectives: Esophageal variceal bleeding (EVB) is a life-threatening complication of portal hypertension, yet many patients experience their first bleeding episode without prior diagnosis or adequate prophylaxis. This study aimed to describe the clinical, laboratory, and radiological findings present one year before the first EVB episode and to examine whether these findings were recognized and acted upon in clinical practice. Methods: We retrospectively reviewed 48 patients admitted with a first episode of EVB between January 2020 and January 2025. Demographic data, laboratory values, abdominal ultrasonography findings, and liver fibrosis scores were recorded both at the time of bleeding and during a baseline period of 12 ± 3 months prior to bleeding. Results: Of 48 patients, 22.9% (n = 11) had not been diagnosed with cirrhosis prior to bleeding, and 33.3% (n = 16) remained without primary prophylaxis despite a known diagnosis—meaning that 56.2% experienced their first EVB without effective preventive management. At baseline, splenomegaly was present in 90% of patients with available ultrasonography data, and 72.9% had platelet counts below 150 × 103/µL. Annual changes in clinical scores (expressed as delta values) demonstrated progressive hepatic deterioration during the unmonitored period, as evidenced by worsening Child–Pugh and MELD scores. Conclusions: In the majority of patients who experienced a first EVB episode, simple and routinely available findings—namely splenomegaly and thrombocytopenia—were already present one year before the bleeding event. Furthermore, delta values indicate that disease severity progressively worsened during this unrecognized at-risk period. These findings represent missed clinical opportunities for earlier diagnosis and initiation of prophylaxis.